The Effects of Microfluidic Sperm Sorting, Density Gradient and Swim-up Methods on Semen Oxidation Reduction Potential - Gode, Funda; Gürbüz, Ali Sami; Tamer, Burcu; Pala, Ibrahim; Isik, Ahmet Zeki (Urology Journal, 2020)
Purpose: To compare the effects of microfluidic sperm sorting, density gradient and swim-up methods on the oxidative reduction potential (ORP) of split semen samples from a single patient population. Materials and Methods: A prospective controlled study was conducted to compare the effects of three different semen processing methods using split semen samples from the same population of infertile men. The primary outcome was the ORP. Secondary outcomes were the sperm concentration, progressive motility rate and total sperm motility. Results: A total of 57 split semen samples were included in this study. The ORP was significantly lower in the microfluidic group compared to the density gradient and swim-up groups (P < 0.05). The ORP/sperm concentration ratio was significantly lower in the microfluidic and density gradient groups compared to the swim-up group (P < 0.05). Total sperm concentration was significantly higher in the density gradient group than the microfluidic and swim-up groups (P < 0.05). Motility was significantly higher in the microfluidic and swim-up groups than the density gradient group (P < 0.05). The progressive motile sperm rate was significantly higher in the microfluidic and swim-up groups than the density gradient group (P < 0.05). Conclusion: Microfluidic sperm sorting was better for selecting highly motile sperm and yielded a lower ORP than conventional sperm preparation methods.